The Implementation of Indonesian National Health Insurance Programme: How Satisfiedwere the Insured Participants and The Healthcare Providers? - Eva Yusuf; Irma Awwaliyah (Journal of Consumer Sciences, 2018)
This study examined how satisfied the insured participants and the healthcare providers were with the services provided by the BPJS Health. The study took place in 24 cities/districts in Indonesia. The data was collected through face-to-face interviews with 17,820 insured participants and 1,170 healthcare providers.The survey revealed that the participantswere satisfied with the services they had obtained from the providers. However, the participants at the primary healthcare facilities hada significantly lower satisfaction level than those at the secondary healthcare facilities. Better facilities and medical equipment, better services from medics and paramedics, better drugs availability and quality, along with assurance in obtaining a proper and timeline treatment, all contributed to the higher satisfaction level. Policy makers need to consider making an improvement on the facilities and service qualities at the primary healthcare facilities in order to enhance the participants’ trust. Otherwise, the referral system implementation under the NHI system might not be effectively implemented as participants prefer to get a treatment from secondary healthcare facilities. This study suggests that empathy attributes are the key factor in building satisfaction level. Special attentions need to be given on the “human” aspect of the service providers.